Endovascular Management of Arteriovenous Malformations of the Brain - Bruno, Charles A. (S. Karger AG, 2013)
Arteriovenous malformations (AVMs) of the brain are rare, complex, vascular lesions that can result in significant morbidity and mortality. Modern treatment of brain AVMs is a multimodality endeavor, requiring a multidisciplinary team with expertise in cerebrovascular neurosurgery, endovascular intervention, and radiation therapy in order to provide all therapeutic options and determine the most appropriate treatment regimen depending on patient characteristics and AVM morphology. Current therapeutic options include microsurgical resection, radiosurgery (focused radiation), and endovascular embolization. Endovascular embolization is primarily used as a preoperative adjuvant before microsurgery or radiosurgery. Palliative embolization has been used successfully to reduce the risk of hemorrhage, alleviate clinical symptoms, and preserve or improve neurological function in inoperable or nonradiosurgical AVMs. Less frequently, embolization is used as ‘primary therapy’ particularly for smaller, surgically difficult lesions. Current embolic agents used to treat brain AVMs include both solid and liquid agents. Liquid agents including N-butyl cyanoacrylate and Onyx are the most commonly used agents. As newer embolic agents become available and as microcatheter technology improves, the role of endovascular treatment for brain AVMs will likely expand.